Quality of life and its predictive factors among women with obstetric fistula in Ethiopia: A cross-sectional study - Hurissa, Bekana Fekecha; Koricha, Zewdie Birhanu; Dadi, Lelisa Sena (Frontiers in Public Health, 2022)
Objective Living with obstetric fistulas is detrimental to the quality of life of women with fistulas. This study aimed to assess the quality of life and predictive factors among women with obstetric fistula in Ethiopia. Methods A cross-sectional study was employed on consecutively selected 478 women. Linear regressions were used for data analysis. Results The mean quality of life in physical, psychological, social, and environmental health domains and the overall quality of life were 40.59 ± 1.58, 38.10 ± 1.78, 29.59 ± 1.97, 34.21 ± 1.65, and 44.61 ± 3.99 respectively. Repair outcome without urinary inconsistence (β = 5.2; 95% CI = 0.72, 9.64), self-esteem (β = 1.3; 95% CI = 0.96, 1.57), negative attitude (β = 5.1; 95% CI = 1.86, 8.33), waiting treatment (β = −8.4; 95% CI = −15.54, −1.10), and low intention (β = 4.7; 95% CI = 1.52, 7.93) were predictors of the quality of life in physical domain. Repair outcome without urinary inconsistence (β = 5.9; 95% CI = 1.73, 9.99), self-esteem (β = 1.8; 95% CI = 1.47, 2.11), negative attitude (β = −6.4; 95% CI = −9.60, −3.25), fathers at primary school (β = 12.5; 95% CI = 0.08, 24.82), living only with parents (β = 4.9; 95% CI = 0.99, 8.90), time of care-seeking (β = −0.01, 95% CI = −0.02, −0.002), and duration lived with fistula (β = −5.4; 95% CI = −9.12, −1.68) were predictors of psychological domain. Dead birth (β = −5.2; 95% CI = −9.86, −0.51), self-esteem (β = 1.1; 95% CI = 0.72, 1.43), and living only with parents (β = 5.5; 95% CI = 0.30, 10.69), and living only with husband (β = 7.8; 95% CI = 2.01, 13.55) were predictors of social domain. Living in rural (β = −6; 95% CI = −9.22, −2.79), women at secondary school (β = 14.1; 95% CI = 3.67, 24.48), self-esteem (β = 1.3; 95% CI = 0.99, 1.55), negative attitude (β = −5.1; 95% CI = −7.97, −2.29) were predictors of quality of life in environmental domain. Repair outcome without urinary inconsistence (β = 8.3; 95% CI = 0.62, 16.02), self-esteem (β = 2.1; 95% CI = 1.34, 2.79), and living only with parents (β = 2.9; 95% CI = 1.06, 4.76) were significant predictors of the overall quality of life. Conclusions The quality of life of women with obstetric fistula was low. Repair outcomes, self-esteem, negative attitudes, rural residence, living with parents, and time of care-seeking were significant predictors of quality of life. Urgent measures should be taken to address these factors to improve the quality of life of women with fistula.